Screening of papaya accessions resistant to Papaya lethal yellowing virus and capacity of Tetranychus urticae to transmit the virus - Basso, Marcos Fernando; Pereira, Álvaro Júlio; Pereira, Hermano Monteiro de Barros; Ramos, Humberto Josué de Oliveira; Dantas, Jorge Luiz Loyola; Fontes, Elizabeth Pacheco Batista; Andrade, Eduardo Chumbinho de; Zerbini, Francisco Murilo (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to produce a polyclonal antiserum against the coat protein (CP) of Papaya lethal yellowing virus (PLYV) and to determine its specificity and sensibility in the diagnosis of the virus, as well as to evaluate the genetic resistance to PLYV in papaya (Carica papaya) accessions and to investigate the capacity of the two‑spotted spider mite Tetranychus urticae to acquire and transmit PLYV to the plants. Sixty‑five papaya accessions were evaluated. For each accession, ten plants were mechanically inoculated using PLYV‑infected plant extracts, and three plants were mock inoculated with phosphate buffer alone and used as negative controls. Ninety days after inoculation, newly‑emerging systemic leaves were collected from the inoculated plants, and viral infection was diagnosed by indirect Elisa, using polyclonal antiserum sensible to the in vitro‑expressed PLYV CP. Viral transmission by T. urticae was evaluated in greenhouse. The experiments were repeated twice. Polyclonal antiserum recognized the recombinant PLYV CP specifically and discriminated PLYV infection from infections caused by other plant viruses. Out of the 65 papaya accessions evaluated, 15 were considered resistant, 18 moderately resistant, and 32 susceptible. The two‑spotted spider mite T. urticae was capable of acquiring PLYV, but not of transmitting it to papaya.